2013
DOI: 10.1117/12.2010846
|View full text |Cite
|
Sign up to set email alerts
|

Joint calibration of 3D resist image and CDSEM

Abstract: Traditionally, an optical proximity correction model is to evaluate the resist image at a specific depth within the photoresist and then extract the resist contours from the image. Calibration is generally implemented by comparing resist contours with the critical dimensions (CD). The wafer CD is usually collected by a scanning electron microscope (SEM), which evaluates the CD based on some criterion that is a function of gray level, differential signal, threshold or other parameters set by the SEM. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The authors adopted the quasi-3D resist model approach to obtain the resist sidewall angle and to mitigate the wafer-to-model errors [1]. Samy et al demonstrated a rigorous resist model calibration and the verification with top-down CD SEM, AFM and cross-section SEM [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors adopted the quasi-3D resist model approach to obtain the resist sidewall angle and to mitigate the wafer-to-model errors [1]. Samy et al demonstrated a rigorous resist model calibration and the verification with top-down CD SEM, AFM and cross-section SEM [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are many rigorous simulators capable of catching the resist profile very well, none of them is feasible for full-chip application due to the tremendous consumption of computational resource. The authors have proposed a quasi-3D image simulation method in the previous study [1], which is suitable for full-chip simulation with the consideration of sidewall angles, to improve the model accuracy of planar models.In this paper, the quasi-3D image simulation is extended to directly model the resist profile with AFM and/or cross-section SEM data. Resist weak points detected by the model generated with this 3D approach are verified on the wafer.…”
mentioning
confidence: 99%
See 1 more Smart Citation